Ducklings and rice, a different recipe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Researchers at the Can Tho University in Vietnam have quantified the efficiency of rearing ducklings in a rice paddy. They put ducklings (100/ha) in rice fields 22 days after sowing and removed them again when the rice started to flower. The...